Chemogenomic analysis reveals key role for lysine acetylation in regulating Arc stability - Jasmin Lalonde (Nature Portfolio, 2017)
The activity-regulated cytoskeleton-associated protein (Arc) has been implicated in synaptic plasticity and memory consolidation. Here the authors show that Arc acetylation regulates its stability and identify small molecules that modulate Arc expression.